Striatal Hand Deformities in Parkinson's Disease: Hand Surgical Perspectives. Issue 8 (22nd August 2022) - Brogren, Elisabeth; Dahlin, Lars B.; Franzen, Erika; Lindholm, Beata
ABSTRACT: Background: The knowledge about striatal hand deformities (SHD) in Parkinson's disease (PD), has recently increased but need more attention due to their early impact on dexterity. The focus of clinical studies has been on the staging of SHD severity and neurological features. However, a hand surgical perspective has not been considered. Objectives: Our purpose was to examine SHD in patients with PD using hand surgical assessment methods and the recommended staging of SHD. Methods: In this observational study, a specialist in neurological physiotherapy examined 100 consecutive PD patients and identified 35 with suspected SHD, who were then examined by two hand surgeons. Their hands were clinically evaluated for severity of SHD, according to a previous proposed staging, focusing on metacarpophalangeal (MCP) joint flexion, presence of intrinsic and extrinsic tightness, as well as other hand deformities. Results: Three kinds of deformities were identified among 35 included patients: surgical diagnoses unrelated to PD (n = 5), SHD (n = 23), and PD related hand deformities with increased extrinsic tightness (n = 10); three of these 10 patients had also contralateral SHD, thus are included in SHD group. In addition to previously described MCP joint flexion, swan neck deformity and z‐thumb deformity, we found in most hands finger "clefting, " abduction of the little finger and/or an increased intrinsic tightness, indicating pathology of intrinsic muscles of the hand involved in SHD. Conclusions: SHD diagnosed with a modified staging method, including features of intrinsic and extrinsic hand deformities, should be considered in PD to implement early and more accurate treatment.